ALVEOLAR RECRUITMENT MANEUVERS FOR CHILDREN WITH CANCER AND ACUTE RESPIRATORY DISTRESS SYNDROME: A FEASIBILITY STUDY - Galassi,Marcela Salvador (2021)
ABSTRACT Objective: Acute respiratory distress syndrome (ARDS) can be a devastating condition in children with cancer and alveolar recruitment maneuvers (ARMs) can theoretically improve oxygenation and survival. The study aimed to assess the feasibility of ARMs in critically ill children with cancer and ARDS. Methods: We retrospectively analyzed 31 maneuvers in a series of 12 patients (median age of 8.9 years) with solid tumors (n=4), lymphomas (n=2), acute lymphoblastic leukemia (n=2), and acute myeloid leukemia (n=4). Patients received positive end-expiratory pressure from 25 up to 40 cmH20, with a delta pressure of 15 cmH2O for 60 seconds. We assessed blood gases pre- and post-maneuvers, as well as ventilation parameters, vital signs, hemoglobin, clinical signs of pulmonary bleeding, and radiological signs of barotrauma. Pre- and post-values were compared by the Wilcoxon test. Results: Median platelet count was 53,200/mm3. Post-maneuvers, mean arterial pressure decreased more than 20% in two patients, and four needed an increase in vasoactive drugs. Hemoglobin levels remained stable 24 hours after ARMs, and signs of pneumothorax, pneumomediastinum, or subcutaneous emphysema were absent. Fraction of inspired oxygen decreased significantly after ARMs (FiO2; p=0.003). Oxygen partial pressure (PaO2)/FiO2 ratio increased significantly (p=0.0002), and the oxygenation index was reduced (p=0.01), but all these improvements were transient. Recruited patients’ 28-day mortality was 58%. Conclusions: ARMs, although feasible in the context of thrombocytopenia, lead only to transient improvements, and can cause significant hemodynamic instability.